Phytochemical Studies on Cissus Glauca - Abraham, G.T.; Shafi, P.M. (Asian Journal of Chemistry, 2010)
Friedelin and a mixture of long chain fatty acid esters were isolated and identified from Cissus glauca (Vitaceae) by chemical and physical methods.